Brake Current Control System Modeling Using Linear Quadratic Regulator (LQR) and Proportional integral derivative (PID) - Anggara Trisna Nugraha; Oktavinna Dwi Pratiwi; Reza Fardiyan As’ad; Vijay Anant Athavale (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
This paper provides a comparative analysis between PID control as a classical control technique and modern control technique in the dinamometer Eddy current brakes system. Eddy current brakes is a modern braking system that requires a control system to support the braking performance. PID control is often used to be implemented but in some conditions it is less optimal. Therefore, it is necessary to develop a modern and optimal control, such as a full state feedback Linear Quadratic Regulator (LQR). The comparison of the braking time responses were simulated using Matlab/Simulink. The simulation results show that the response of LQR control is better than the PID, with Ts = 2.12 seconds, Tr = 1.18 seconds, and without overshoot. On the other side, PID control, although having Ts = 0.27 seconds and Tr = 0.18 seconds, there is still an overshoot about 0.7%.